Metode Penerjemahan QS. Luqman Ayat 13-15 Tentang Pendidikan Anak: Studi Komparatif Terjemahan Kementerian Agama 2019 dan Tarjamah Tafsiriyah - Reza Alpandi; Rinaldi Supriadi (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to identify the translation methods used in both translations and to analyse the trends in their translation orientation when representing messages on children’s education. This study employs a qualitative approach with a comparative study design. The research data consist of linguistic units from Surah Luqman, verses 13–15, which were analysed using Newmark’s (1988) theory of translation methods. The results indicate that the Indonesian Ministry of Religious Affairs’ translation predominantly employs literal and semantic methods oriented towards the source language, thus tending to preserve the structure, formality and closeness of meaning to the original text of the Qur’an. Conversely, Tarjamah Tafsiriyah predominantly employs communicative and free methods through the explicitation of meaning and the adaptation of the target language’s structure. These differing orientations result in variations in the representation of messages regarding children’s education within the translated texts. Tarjamah Tafsiriyah tends to present messages more explicitly by adding contextual elements of meaning, whilst the Indonesian Ministry of Religious Affairs’ translation places greater emphasis on preserving the meaning and form of the source text. The findings of this study indicate that differences in translation methods result in differences in the representation of educational messages for children in these two translations of the Qur’an.